Three‐dimensional magnetic flux rope structure formed by multiple sequential X‐line reconnection at the magnetopause. Issue 5 (28th May 2013) - Zhong, J.; Pu, Z. Y.; Dunlop, M. W.; Bogdanova, Y. V.; Wang, X. G.; Xiao, C. J.; Guo, R. L.; Hasegawa, H.; Raeder, J.; Zhou, X. Z.; Angelopoulos, V.; Zong, Q. G.; et al.
Abstract : [1] On 14 June 2007, four Time History of Events and Macroscale Interactions during Substorms spacecraft observed a flux transfer event (FTE) on the dayside magnetopause, which has been previously proved to be generated by multiple, sequential X‐line reconnection (MSXR) in a 2‐D context. This paper reports a further study of the MSXR event to show the 3‐D viewpoint based on additional measurements. The 3‐D structure of the FTE flux rope across the magnetospheric boundary is obtained on the basis of multipoint measurements taken on both sides of the magnetopause. The flux rope's azimuthally extended section is found to lie approximately on the magnetopause surface and parallel to the X‐line direction; while the axis of the magnetospheric branch is essentially along the local unperturbed magnetospheric field lines. In the central region of the flux rope, as distinct from the traditional viewpoint, we find from the electron distributions that two types of magnetic field topology coexist: opened magnetic field lines connecting the magnetosphere and the magnetosheath and closed field lines connecting the Southern and Northern hemispheres. We confirm, therefore, for the first time, the characteristic feature of the 3‐D reconnected magnetic flux rope, formed through MSXR, through a determination of the field topology and the plasma distributions within the flux rope. Knowledge of the complex geometry of FTE flux ropes will improve our understanding of solar wind‐magnetosphere interaction. Key Points: Both open and closed field line geometries co‐exist in the FTE flux ropes Observation of 3D flux rope structure across the magnetopause Formation of the magnetospheric boundary layer of closed field lines